Pengembangan Pariwisata Budidaya Ikan Konsumsi Desa Potorono, Kapanewon Banguntapan, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Kurnianingtyas, Chandra Dewi (Jurnal Atma Inovasia, 2022)
KKN 80 Atma Jaya University Yogyakarta chose Bantul and Potorono Regencies as locations to implement the Community 5.0 Community Service Program. This KKN 80 activity aims to help the residents of Potorono Village explore and look for village potentials that can be developed in order to provide added value to the village. The author has an idea to develop the potential of the village in the field of fish farming. Fish farming is very suitable to be developed in Potorono Village because Potorono Village has a large lake. The service method used is counseling, the author also seeks information related to the village's potential. The author plans to make innovations regarding the development of consumption fish farming tourism in Potorono Village, there is a potential reservoir that can implement this development. The results of the development of consumption fish farming tourism are in the form of fish and tourism. The counseling stage for the development of consumption fish farming tourism will be documented in the form of e-books and interactive videos, in order to make it easier for the residents of Potorono Village to realize it and it is expected to grow the tourism economy in Potorono Village.